Effect of "fasting" and different concentrations of glucose on alpha-linolenic acid metabolism in HTC cells: correlation with the ultrastructural study - Gómez Dumm, César Leandro Alberto (1977)
HTC cells are able to convert α-linolenic acid into higher homologs by desaturating and elongating reactions. When the cells were cultured in a Krebs Ringer bicarbonate solution (“fasted cells”) a decrease in both biosynthetic reactions took place. “Refeeding” the cells with Swim's 77 medium without glucose enhanced the biosynthesis of polyunsaturated fatty acids from α-linolenic acid family, but when glucose was added to the medium, α-linolenic acid was preferably elongated rather than converted into eicose-pentaenoic acid. The ultrastructural study revealed HTC cells with a simple cytoplasmic organization, showing little evidence of their origin from hepatocytes. The cells cultured in a complete medium appeared well preserved and were similar to those “fasted” for 12 hours and “refed” for another 12 hours using Swim's 77 medium without serum. The amount of glucose in the medium plays a role in preserving the cell structure. This effect does not occur if glucose is added in the absence of aminoacids and vitamins.